High BIN1 expression has a favorable prognosis in malignant pleural mesothelioma and is associated with tumor infiltrating lymphocytes. (April 2019) - Ahmadzada, Tamkin; Lee, Kenneth; Clarke, Candice; Cooper, Wendy A; Linton, Anthony; McCaughan, Brian; Asher, Rebecca; Clarke, Stephen; Reid, Glen; Kao, Steven
Highlights: High BIN1 expression has a favorable prognosis in malignant pleural mesothelioma (MPM). High BIN1 expression is associated with tumor-infiltrating lymphocytes (TILs). Expression of CD68+ macrophages is an adverse prognostic factor in MPM. MPM is characterized by TILs regardless of presence of other adverse prognostic factors. Abstract: Objectives: A number of key immune regulators show prognostic value in malignant pleural mesothelioma (MPM), but the association between Bridging integrator 1 (BIN1), indoleamine 2, 3 dioxygenase 1 (IDO1) and patient outcome has not been investigated. We aimed to determine the expression of BIN1 and IDO1, their association with other markers and impact on overall survival (OS) in MPM. Materials and methods: The expression of BIN1, IDO1, CD3, CD20 and CD68 were evaluated by immunohistochemistry in 67 patients who underwent pleurectomy/decortication. Survival analyses were performed using the Kaplan Meier method and significant biomarkers were entered into a Cox Regression multivariate model, accounting for known prognostic factors such as age, gender, histological subtype, PD-L1 expression and neutrophil-to-lymphocyte ratio. Results: Immune markers were variably expressed in tumor cells, ranging from 0% to 100% for BIN1 (median: 89%), and 0% to 77.5% for IDO1 (median: 0%). Expression of markers of tumor-infiltrating lymphocytes (TILs) and macrophages ranged from 0% to more than 50%. BIN1 expression was high in 35 patients (51%) and was associated with increased OS (median: 12 vs 6 months for high and low BIN1 respectively, p = 0.03). Multivariate analysis showed BIN1 remained an independent prognostic indicator (HR 0.39; 95% CI: 0.18-0.82, p = 0.01). The majority of patients had immune inflamed tumors (77%) and there was a significant association between TILs and BIN1 ( p = 0 < 0.01), PD-L1 ( p= 0.04) and CD68+ macrophages in the tumor ( p < 0.01). There were no significant associations between PD-L1 and BIN1 or IDO1. Conclusion: High BIN1 expression is a favorable prognostic biomarker and is associated with TILs in MPM.